Schématisation et description du fonctionnement de la communication dans les ateliers-philo en contexte scolaire - Aline Auriel (Recherches en Éducation)
Through this paper, we propose to draw up a model of philosophical discussion as a particular situation of communication, in order to understand the functioning of the communication in these spaces of collective thinking. We adopt a systemic-constructivist-interactionist approach, pointing out the importance of a global view of communication, rather than focusing on each exchange. This vision enables us to describe the functioning of teacher-student and student-student interactions, in the philosophical discussion; and to identify the element to take into account in the analysis, such as differents contexts of philosophical discussion, for example.